The HOPE Asia Network activity 2022: Towards better hypertension management in Asia - Kario, Kazuomi; Chia, Yook Chin *; Wang, Ji-Guang (Wiley, 2022)
Welcome to the third special Asia issue of Journal of Clinical Hypertension. This follows on from the success of the first two Asia special issues, published in 2020 and 2021. An important driver for hypertension research and guidance in the Asian region is the Hypertension Outcome Prevention and Evidence in Asia (HOPE Asia) Network, which has published a variety of resources and research, starting in 2017 with a statement on home blood pressure monitoring (HBPM).1 More recently, the HOPE Asia Network has released guidance on the management of hypertension in the context of the coronavirus disease 2019 (COVID-19) pandemic.2 This pandemic has limited face-to-face interactions, not only between clinicians and their patients, but also among colleagues and researchers. Despite these challenges, the HOPE Asia Network has continued to work and collaborate remotely to allow the important task of improving hypertension management in Asia to continue.